2019
DOI: 10.3389/fnins.2019.00632
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss and Cognition Among Older Adults in a Han Chinese Cohort

Abstract: Presbycusis (PC) is associated with cognitive decline and incident dementia. Speech reception thresholds (SRT) are used to assess speech detection, which points toward a central component of PC. However, to the best of our knowledge, no previous study has reported the relationship between SRT and cognitive function in older adults in a Han Chinese cohort. Therefore, in this study, we investigate the association of hearing loss, indexed using pure tone average (PTA) and SRT, with cognitive function in a Han Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 32 publications
4
24
0
6
Order By: Relevance
“…Findings related to group differences revealed that ARHL group demonstrated not only slower, but also worse, inhibitory control. On the Stroop color-word interference condition, the ARHL group took longer to complete the task relative to the NH group, which is consistent with the findings of most prior studies [37,39,59], with two exceptions [38,59]. Our finding suggests that the ARHL group required more time to successfully employ inhibitory control to perform the task with the same accuracy level as the NH group.…”
Section: Inhibitionsupporting
confidence: 90%
See 4 more Smart Citations
“…Findings related to group differences revealed that ARHL group demonstrated not only slower, but also worse, inhibitory control. On the Stroop color-word interference condition, the ARHL group took longer to complete the task relative to the NH group, which is consistent with the findings of most prior studies [37,39,59], with two exceptions [38,59]. Our finding suggests that the ARHL group required more time to successfully employ inhibitory control to perform the task with the same accuracy level as the NH group.…”
Section: Inhibitionsupporting
confidence: 90%
“…These processes are not specific to a particular modality, such as visual or auditory. In the context of ARHL, studies have predominantly investigated alterations in cognitive control processes by examining their associations with measures of peripheral hearing, primarily pure-tone average (PTA) [23,24,28,[34][35][36][37][38][39][40], with some recently examining associations with central hearing measures, particularly SiN recognition [35,[41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations